Zircon and apatite fission track analyses: new insight about the exhumation of Cordillera del Viento, Neuquén Basin, Argentina - Pons, María Josefina (2022)
Fil: Pons, Josefina. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.